Review—Energy Autonomous Wearable Sensors for Smart Healthcare: A Review. Issue 3 (1st January 2020) - Dahiya, Abhishek Singh; Thireau, Jerome; Boudaden, Jamila; Lal, Swatchith; Gulzar, Umair; Zhang, Yan; Gil, Thierry; Azemard, Nadine; Ramm, Peter; Kiessling, Tim; O'Murchu, Cian; Sebelius, Fredrik; et al.
Abstract : Energy Autonomous Wearable Sensors (EAWS) have attracted a large interest due to their potential to provide reliable measurements and continuous bioelectric signals, which help to reduce health risk factors early on, ongoing assessment for disease prevention, and maintaining optimum, lifelong health quality. This review paper presents recent developments and state-of-the-art research related to three critical elements that enable an EAWS. The first element is wearable sensors, which monitor human body physiological signals and activities. Emphasis is given on explaining different types of transduction mechanisms presented, and emerging materials and fabrication techniques. The second element is the flexible and wearable energy storage device to drive low-power electronics and the software needed for automatic detection of unstable physiological parameters. The third is the flexible and stretchable energy harvesting module to recharge batteries for continuous operation of wearable sensors. We conclude by discussing some of the technical challenges in realizing energy-autonomous wearable sensing technologies and possible solutions for overcoming them.